The Effect of Good Corporate Governance on Financial Performance in Conventional and Islamic Banks: An Empirical Studies in Indonesia - Purwanto, Purwanto; Bustaram, Isnain; Subhan, Subhan; Risal, Zef (International Journal of Economics and Financial Issues, 2020)
This study discusses about good corporate governance implementation which in this study includes managerial ownership, institutional ownership, and audit committee which rated as capable to improve the images on banking which were bad, protect the stakeholder interest, and increasing the obedience to applicable laws and regulation and also general etiquette in banking industry in imaging banking system that is through company financial performance. The population of this study is all conventional and Islamic banking listed in Indonesia Stock Market throughout 2016-2018, sample that is used are 42 companies which have published their financial report from 2016-2018 continuously. The study result shows the managerial ownership variable has 0.02 significant effect towards financial performance, institutional ownership variable has 0.049 significant value towards financial performance, audit committee variable has 0.031 significant value towards financial performance. Meanwhile, they are simultaneously having 0.031 significant value towards financial performance. Keywords: managerial ownership, institutional ownership, audit committee, financial performance. JEL Classifications: M4, G38, G2, G3 DOI: https://doi.org/10.32479/ijefi.9139